A map of evidence using transcranial direct current stimulation (tDCS) to improve cognition in adults with traumatic brain injury (TBI) - Julie Lynn Schwertfeger; Julie Lynn Schwertfeger; Charlotte Beyer; Paul Hung; Paul Hung; Nathaniel Ung; Caroline Madigan; Alvi Renzyl Cortes; Bharathi Swaminathan; Bharathi Swaminathan; Sangeetha Madhavan (Frontiers in Neuroergonomics, 2023)
IntroductionCognition impairments often occur after a traumatic brain injury and occur at higher rates in military members. Cognitive symptoms impair daily function, including balance and life quality, years after the TBI. Current treatments to regain cognitive function after TBI, including medications and cognitive rehabilitation, have shown limited effectiveness. Transcranial direct current stimulation (tDCS) is a low-cost, non-invasive brain stimulation intervention that improves cognitive function in healthy adults and people with neuropsychologic diagnoses beyond current interventions. Despite the available evidence of the effectiveness of tDCS in improving cognition generally, only two small TBI trials have been conducted based on the most recent systematic review of tDCS effectiveness for cognition following neurological impairment. We found no tDCS studies that addressed TBI-related balance impairments.MethodsA scoping review using a peer-reviewed search of eight databases was completed in July 2022. Two assessors completed a multi-step review and completed data extraction on included studies using a priori items recommended in tDCS and TBI research guidelines.ResultsA total of 399 results were reviewed for inclusion and 12 met the criteria and had data extracted from them by two assessors using Google Forms. Consensus on combined data results included a third assessor when needed. No studies using tDCS for cognition-related balance were found.DiscussionGuidelines and technology measures increase the identification of brain differences that alter tDCS effects on cognition. People with mild-severe and acute-chronic TBI tolerated and benefited from tDCS. TBI-related cognition is understudied, and systematic research that incorporates recommended data elements is needed to advance tDCS interventions to improve cognition after TBI weeks to years after injury.